2016
DOI: 10.1186/s13613-016-0136-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of left ventricular diastolic function in patients with septic shock

Abstract: BackgroundLeft ventricular (LV) diastolic dysfunction is highly prevalent in the general population and associated with a significant morbidity and mortality. Its prognostic role in patients sustaining septic shock in the intensive care unit (ICU) remains controversial. Accordingly, we investigated whether LV diastolic function was independently associated with ICU mortality in a cohort of septic shock patients assessed using critical care echocardiography.MethodsOver a 5-year period, patients hospitalized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…The full texts of 480 documents were assessed and 145 studies, reported in 147 records, were eligible for inclusion. Of these, 37 studies reported comparison of delay vs no delay in receiving appropriate therapy and/or time to appropriate therapy 18,22,27,30,32,35,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] and are included in this analysis (Fig 1; e- Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full texts of 480 documents were assessed and 145 studies, reported in 147 records, were eligible for inclusion. Of these, 37 studies reported comparison of delay vs no delay in receiving appropriate therapy and/or time to appropriate therapy 18,22,27,30,32,35,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] and are included in this analysis (Fig 1; e- Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Three prospective cohort studies, 20,24,31 32 retrospective cohort studies, [15][16][17][18][19][21][22][23][25][26][27][28][29][30]32,33,35,36,[38][39][40][41][42][43][44][45][46][47][48][49][50][51] and two casecontrol studies 34,37 were included. Two studies were carried out internationally 16,44 and 35 in single countries across Europe, 22,24,31,34,38,43 Asia, 16,20,21,23,25,26,…”
Section: Description Of Studiesmentioning
confidence: 99%
“…But why is there so much interest in diastolic dysfunction in the ICU population? We think it might be influenced by studies identifying diastolic dysfunction as a predictor of mortality especially in the septic population [1,2,4,[6][7][8]. The 2016 ASE/EACVI guidelines simplify our approach to diastolic dysfunction but they do not solve all diagnostic problems in critically ill and mechanically ventilated patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, several authors investigated the role of echocardiography for the study of septic shock, which could offer important information on cardiac loss of function due to sepsis. It has been shown that in these patients a certain grade of diastolic dysfunction could be detected by power and tissue Doppler imaging (TDI): The most used parameter is transmitral E/E′ ratio, with a lack of defined cutoff value; however, a higher proportion of diastolic dysfunction with values of E′ < 8‐10 cm/s was found to be independently associated with higher risk of death 48 (odds ratio, OR 7.7 of ICU mortality in a study by Mourad et al 49 ). Moreover, advanced echocardiography has shown good results for the evaluation of patients with septic shock: Orde et al demonstrated the superior value of STE over basic echocardiography in 60 patients with septic shock, detecting LV strain and RV strain impairment in 69% and 72% of patients, respectively, with only 33% patients having reduced LV ejection fraction (EF) and 32% having RV dysfunction based on conventional echocardiography (tricuspid annular plane systolic excursion, TDI s′ wave, RV fractional area change); moreover, they found RV‐free wall strain to be moderately associated with 6‐month mortality (OR 1.1, AUC 0.68) 50 .…”
Section: Sepsismentioning
confidence: 99%